Does the type of neighbor matter? Heterogeneous export spillovers on domestic companies in Mexico - Cardoso Vargas, Carlos Enrique (Estudios Económicos de El Colegio de México, 2017)
This document examines whether the probability of entering new external markets or the increase in export products on the part of Mexican firms are related to the proximity of diverse multinational firms exporting under different trade regimes. The results show that export spillovers are far from homogeneous in their effects on Mexican firms, since their existence is related to the export activity of neighboring foreign firms. Moreover, such spillovers are more likely to appear in places where neighboring national and foreign firms have not only common trade regimes, but also common technological level of production.